2017
DOI: 10.1002/rcr2.244
|View full text |Cite
|
Sign up to set email alerts
|

A bronchial fibroepithelial polyp with abnormal findings on auto-fluorescence imaging

Abstract: Bronchial fibroepithelial polyps represent a rare type of tumour that displays endobronchial growth. The findings of these lesions on auto‐fluorescence imaging (AFI) bronchoscopy have not been reported, despite the usefulness of AFI in detecting early lung cancer. We report the case of a patient with a bronchial fibroepithelial polyp that displayed positivity (magenta colour) on AFI. The patient was a 65‐year‐old man, in whom an endobronchial polypoid lesion of 10 mm diameter had been detected in the right bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Saito et al described a 65-year-old man, who was diagnosed with a bronchial fibroepithelial polyp of the right basal bronchus and underwent bronchoscopic examination, with a videobronchoscope that incorporates two devices for white-light (WL) mode and auto-fluorescence imaging (AFI). Bronchoscopy under WL mode revealed a rounded, whitish, smooth, and glistening polypoid lesion with a lobulated surface and on AFI, the lesion appeared magenta colour (positivity) [15]. The authors of this case concluded that bronchial fibroepithelial polyps may display AFI positivity and the right diagnosis should not be confused by this positivity [15].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Saito et al described a 65-year-old man, who was diagnosed with a bronchial fibroepithelial polyp of the right basal bronchus and underwent bronchoscopic examination, with a videobronchoscope that incorporates two devices for white-light (WL) mode and auto-fluorescence imaging (AFI). Bronchoscopy under WL mode revealed a rounded, whitish, smooth, and glistening polypoid lesion with a lobulated surface and on AFI, the lesion appeared magenta colour (positivity) [15]. The authors of this case concluded that bronchial fibroepithelial polyps may display AFI positivity and the right diagnosis should not be confused by this positivity [15].…”
Section: Discussionmentioning
confidence: 74%
“…Bronchoscopy under WL mode revealed a rounded, whitish, smooth, and glistening polypoid lesion with a lobulated surface and on AFI, the lesion appeared magenta colour (positivity) [ 15 ]. The authors of this case concluded that bronchial fibroepithelial polyps may display AFI positivity and the right diagnosis should not be confused by this positivity [ 15 ]. Desai and Bernstein described a 58-year-old male with an endobronchial lesion in the left lower lobe bronchus in bronchoscopy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, 42 cases of endobronchial fibroepithelial polyp are reported. Clinical data are available for 32 patients 4–10. The youngest patient described is a 32-year-old.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Clinical data are available for 32 patients. [4][5][6][7][8][9][10] The youngest patient described is a 32-year-old. Hemoptysis, cough, dyspnea, refractory asthma, or repeated pneumonia are the most frequent clinical presentations.…”
Section: Literature Review and Discussionmentioning
confidence: 99%
See 1 more Smart Citation